Preparation of Citric Acid Crosslinked Chitosan/Poly(Vinyl Alcohol) Blend Membranes for Creatinine Transport - Retno Ariadi Lusiana; Dwi Siswanta; Mudasir Mudasir (Indonesian Journal of Chemistry, 2016)
Preparation of membrane using crosslinking reaction between chitosan and citric acid showed that functional group modification increased the number of active carrier groups which lead to better transport capacity of the membrane. In addition, the substitution of the carboxyl group increased creatinine permeation of chitosan membrane. The transport capacity of citric acid crosslinked chitosan membrane for creatinine was found to be 6.3 mg/L. The presence of cyanocobalamin slightly hindered the transport of creatinine although compounds did not able to pass through citric acid crosslinked chitosan/poly(vinyl alcohol) blend membrane, as compounds no found in the acceptor phase.